Varietal Differences in Food Value of Leaf Blight Infected Mulberry Leaves and their Impact on Economic Characters of Silkworm (Bombyx mori L.) - Ghosh, L; Ali, MR (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Mulberry; nutritional food value; leaf blight disease; Phyllosticta sp.; silkworm Bangladesh j. genet. biotechnol. 5 (1&2): 73-77, 2004 (June & December)